Meshing Stiffness Calculation of Spur Bevel Gears Considering the Tooth Pair Coupling - Li Feifei; Dong Huimin; Zhang Chu (Jixie chuandong)
In order to solve the problem of calculation efficiency and accuracy of time-varying meshing stiffness of spur bevel gears, a slice calculation method of meshing stiffness of spur bevel gears considering the coupling effect of tooth pairs is proposed. Based on the slice discretization method, the bevel gear tooth and the gear body are discretized into several slices with the same width along the tooth width direction and the axis direction respectively, and the slices are expanded based on the back cone equivalence principle. When the slice width is small enough, the bevel gear can be approximated as a series of spur gears, and the meshing stiffness of each slice can be calculated by the energy method. In order to consider the coupling effect of multi-tooth meshing, the correction coefficient of gear stiffness is introduced in the calculation of double tooth meshing stiffness, which reduces the calculation error of double tooth meshing stiffness. The meshing stiffness model of bevel gears under the error condition is established. The meshing stiffness of spur bevel gears, the angular displacement of the center point of each slice and the load distribution of the tooth surface under the ideal and assembly error conditions are calculated and analyzed. Finally, the accuracy and efficiency of the proposed method are verified by comparing with the finite element calculation results.